ANALISIS KUALITATIF SENYAWA FORMALDEHYDE PADA TAHU PUTIH YANG BEREDAR DI PASAR KABUPATEN DAN PASAR KOTA SORONG - Lamarunga, Nur Hasana; Muslihin, A.M.; Astuti, Ratih Arum (JURNAL ETNOFARMASI, 2024)
Tofu is one of the foods that is very popular with people because it has an economical price and sufficient nutrition, but it does not last long. Formalin is known as a synthetic preservative, but there are still many sellers who add formaldehyde to food, one of which is tofu, in order to extend the shelf life. storage. Formalin should not be added to food, even a small amount because it can cause cancer. The aim of the research is to find out whether the tofu circulating in the Regency market and Sorong City market contains qualitative formaldehyde with chromatophic acid reagent because it effectively binds the formaldehyde so that it is released from the ingredients. The research was carried out. at the UNIMUDA Sorong Integrated Laboratory, using a qualitative method with the addition of chromatogenic acid and sulfuric acid reagents then heated for 15 minutes, if there is a change in color to purple then the sample is declared positive for formalin. A total of 21 tofu samples obtained from 7 markets in Sorong Regency and City did not find formalin compounds.